Autonomy support in the aquatic motivational healthy program through the SDT - Ricardo Zazo Sánchez-Mateos; Fernando Peruyero; Juan Antonio Moreno Murcia (Desafio Singular, 2018)
This study aimed to test an aquatic motivation healthy program based on the self determination theory (SDT), using a quasi-experimental study. The research data come from different physical, psycho-social and behavioral measures made on 49 women. The sample was divided into two groups, an experimental group consisting of 28 women (M= 43.64; SD= 12.06), with an average experience of 3.05 years, and a control group composed of 21 women (M= 47.14; SD= 10.01), with an average experience of 2.29 years doing physical exercise in an aquatic environment in a large Spanish city. After the intervention with a program based on the SDT and instructor's autonomy support, both groups perceived physical benefits for health, but the experimental group perceived a better instructor's autonomy support, a better relationship with others and a greater psychological well-being among the practitioners. The information offered in this study may be of interest to promote for instructor part, these type the aquatic physical exercise programs in favor of the population's health.